Chronic exposure to inhaled vaporized cannabis high in Δ9-THC suppresses Adderall-induced brain activity - Jack M. Ognibene; Rajeev I. Desai; Rajeev I. Desai; Praveen P. Kulkarni; Craig F. Ferris; Craig F. Ferris (Frontiers Media S.A., 2024)
BackgroundThere are increasing reports of the misuse of prescription psychostimulants for cognitive enhancement together with recreational cannabis. This raises a concern that chronic use of cannabis high in Δ9-THC may alter the sensitivity to amphetamines. In this exploratory study we hypothesized chronic exposure to Δ9-THC through vaporized cannabis would diminish the central nervous system (CNS) activity of Adderall.MethodsTo address this issue we exposed male and female mice to inhaled vaporized cannabis (10.3% Δ9-THC) or placebo for 30 min each day for ten consecutive days. After 24 h, mice were imaged fully awake for changes in BOLD signal following an IP injection of Adderall (60 µg) during the scanning session. After a 2-week washout, without any cannabis or placebo exposure, mice were again imaged and challenged with Adderall during the scanning session. The data were registered to a mouse 3D MRI atlas with 134 brain regions providing site-specific increases and decreases in global brain activity.ResultsMice exposed to cannabis when compared to placebo showed a decrease in brain activation to Adderall. The blunted Adderall response was characterized by a decrease in positive BOLD signal and increase in negative BOLD. The prefrontal cortex, accumbens, ventral pallidum, caudate/putamen, and thalamus were most affected. After a 2-week wash out there were no significant differences between the cannabis and placebo groups when challenged with Adderall.SummaryThis exploratory study shows that short, daily exposures to inhaled cannabis, something equivalent to recreational use, affects the sensitivity to the psychostimulant Adderall. The reduced Adderall effect on brain activity, particularly circuitry associated with dopaminergic signaling raises concerns about escalation in psychostimulant use.